Desain Kegiatan Laboratorium: Pendekatan Diagram Vee pada Materi Struktur Darah: (Laboratory Activity Design: Diagram Vee Approach on Blood Structure Lesson) - Sofi Rahmania; Sri Anggraeni; Bambang Supriatno (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
It is certain that the Industrial Revolution 5.0 has entered the world of education, so this Industrial Revolution 5.0 is a challenge for the quality of education in Indonesia. One way to improve the quality of education is practicum activities using Laboratory Activity Designs (LAD) that are in accordance with the demands of the curriculum. This study aims to provide an overview of the quality of blood structure LAD in high school and reconstruct it to improve strudents’understanding. This research is a descriptive study and the subject of this research is blood structure LAD. The sampling technique that used is purposive sampling with a total sample of 6 LAD, consisting of 2 LAD from 2006 curriculum or KTSP, 2 LAD from 2013 curriculum, and 2 LAD from 2013 revised 2016 curriculum. The instruments that used are relevance analysis instruments, competency analysis and practical analysis, and knowledge construction analysis. The findings showed that the blood structure LAD was not good yet because there were still problems with competence, practice and knowledge construction. The solution to this problem is to improve the existing LAD and consider it based on the relevant aspects of competency, practicality and knowledge construction. Abstrak. Revolusi Industri 5.0 dapat dipastikan telah memasuki dunia pendidikan, maka revolusi indeustri ke-5 ini menjadi tantangan bagi kualitas pendidikan di Indonesia. Salah satu cara untuk meningkatkan kualitas pendidikan yaitu dengan kegiatan praktikum menggunakan Desain Kegiatan Laboratorium (DKL) yang sesuai dengan tuntutan kurikulum. Penelitian ini bertujuan untuk memberikan gambaran mengenai kualitas DKL struktur darah dan mereonstruksinya guna meningkatkan pemahaman peserta didik. Penelitian ini merupakan penelitian deskriptif dan subjek penelitian ini adalah DKL struktur darah. Teknik sampling yang digunakan yaitu purposive sampling dengan total sampel sebanyak 6 DKL, terdiri dari 2 DKL kurikulum 2006 atau KTSP, 2 DKL kurikulum 2013 dan 2 DKL kurikulum 2013 revisi 2016. Instrumen yang digunakan meliputi instrumen analisis relevansi, analisis kompetensi dan analisis praktikal serta analisis konstruksi pengetahuan. Hasil temuan menunjukkan DKL struktur darah belum baik karena masih terdapat masalah pada aspek kompetensi, praktikal dan konstruksi pengetahuan. Solusi untuk permasalahan ini adalah memperbaiki DKL yang ada dengan pertimbangan aspek relevansi, kompetensi, praktikal dan konstruksi pengetahuan.